2017
DOI: 10.1111/ceo.13038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and social characteristics associated with reduced visual acuity at presentation in Australian patients with neovascular age‐related macular degeneration: a prospective study from a long‐term observational data set. The Fight Retinal Blindness! Project

Abstract: Poor presenting vision is detrimental to the long-term outcomes of nAMD. Poor presentation of nAMD in Australia may not be related to socio-economic circumstances, but due to systems of care. Further research is warranted to determine why patients at public practices present with worse vision compared with private practices in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Additional factors include socio-economic status and resource allocation with deprivation being related to worse ocular health outcomes. 62 , 63…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors include socio-economic status and resource allocation with deprivation being related to worse ocular health outcomes. 62 , 63…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors include socioeconomic status and resource allocation with deprivation being related to worse ocular health outcomes. 62,63 Choosing the right parameters to judge the quality of a good service is an important consideration. Looking just at mean VA gain could penalize services that have good referral mechanisms in place and start with better baseline VA.…”
Section: Inter-centre and Intra-centre Variation In Visual Outcomesmentioning
confidence: 99%
“…Unlike the findings of this study, Acharya et al 4 did not found an association between the SES and baseline VA of the first eye as a binary or continuous variable in 240 patients with nvAMD from the United Kingdom. Similarly, Nguyen et al 12 did not found connection between SES and VA at presentation in Australia. On the other hand, More et al 13 found similar results to the ones described in this study with patients from lower SES having lower VA at presentation.…”
Section: Discussionmentioning
confidence: 88%
“…The analysis was done by considering SES cluster as a continuous variable and also by grouping SES into four categories (category 1 ¼ cluster 1-5, category 2 ¼ cluster 6-10, category 3 ¼ cluster 11-15, category 4 ¼ cluster 16-20). As detailed in the "Results" section, for some of the clinical parameters, analysis was done comparing between the lower cluster (1)(2)(3)(4)(5) and the rest (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and by dividing the scale into two parts (1-10 and 11-20).…”
Section: Methodsmentioning
confidence: 99%
“…[1314] Australian studies have shown AMD to be a significant contributor to blindness and visual impairment in Australian population. [15] This in turn demands increased proficiency in retinal diagnosis and treatment. [16] The high prevalence of diabetes in India can translate into a large number of people with DR.…”
Section: Discussionmentioning
confidence: 99%